Interdependence of Physical (In-) Activity, Fitness and Cognition: A Cross-Sectional Study in Young Adults - Krell-Rösch, Janina (Karlsruher sportwissenschaftliche Beiträge / Institut für Sport und Sportwissenschaft, Karlsruher Institut für Technologie (KIT). Hrsg.: Prof. Dr. Klaus Bös, PD Dr. Michaela Knoll, 2014)
There is growing evidence for possible associations between physical exercise, fitness and cognitive performance in elderly, but research in young adults is lacking. The aim of this cross-sectional study was to investigate the interdependence between physical (in-) activity, fitness, and cognition in young adults. The methods included a number of physical performance tests, a physical activity questionnaire, and a test battery to measure executive functions and event-related brain potentials.